Can smart policies reconcile Singapore's green economy with sand imports from Southeast Asia? - Michael Hübler; Frank Pothen (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2018)
This article tries to increase public awareness of a crucial but rarely discussed global challenge by introducing a novel economic analysis: drawing on insights from various disciplines, it studies policies regulating sand extraction and trade. While sand is essential for construction and land reclamation worldwide, its extraction causes severe ecological damage in oceans, in rivers and on beaches and thus has high social costs. To derive solutions to this paramount global challenge, this article focuses on sand exports from developing countries in Southeast Asian to Singapore as a prominent example. It evaluates output, export and import taxes as the means to reduce sand extraction and trade. To this end, it utilizes an Eaton and Kortum type trade model within a general equilibrium framework. Overall, an output tax can reduce sand extraction to a large extent, while the economic costs are small for Singapore and slightly positive for the Southeast Asian sand exporters. As a novel policy, the sand tax can be implemented as a Sand Extraction Allowances Trading Scheme (SEATS). This policy can help sustainably balance Singapore's economic growth with Southeast Asia's economic development.
Keywords: F13; Q02; 330; Sand extraction; trade policy; Singapore; Eaton-Kortum trade model